2010
DOI: 10.1021/jp912133r
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electron-Transfer Dynamics from Coumarin 343 to TiO2, SnO2, and ZnO Nanocrystalline Thin Films: Role of Interface-Bound Charge-Separated Pairs

Abstract: The role of the interface-bound charge-separated pair (IBCSP) in electron transfer at molecule/inorganic semiconductor interface remains poorly understood despite the importance of its counterpart in the solution-phase charge-separation process. To probe their role, we have compared the dynamics of electron transfer from C343 to TiO2, SnO2, and ZnO nanocrystalline thin films. The decay of the C343 excited state and the formation of oxidized C343 are measured by transient visible absorption to follow the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
110
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(126 citation statements)
references
References 67 publications
16
110
0
Order By: Relevance
“…1. Further, this same assumption has been employed previously by Lian and coworkers in an investigation of electron transfer rate constants between organic dyes and metal oxide nanoparticles, which reported good agreement between the many-state Marcus formula and experimental findings (13).…”
Section: Modeling Electron Transfer In Qd-mo Nanoparticulate Systemssupporting
confidence: 56%
See 1 more Smart Citation
“…1. Further, this same assumption has been employed previously by Lian and coworkers in an investigation of electron transfer rate constants between organic dyes and metal oxide nanoparticles, which reported good agreement between the many-state Marcus formula and experimental findings (13).…”
Section: Modeling Electron Transfer In Qd-mo Nanoparticulate Systemssupporting
confidence: 56%
“…Later, this model was extended to describe electron transfer from a single donating state to a continuum of accepting states, such as those present in the conduction band of a semiconductor (12). This model, which has been used to successfully describe the dependence of electron transfer rate on free energy driving force for systems of organic dyes coupled to various metal oxides (13)(14)(15)(16)(17)(18), has yet to be applied to a quantized semiconducting nanocrystal donor and nanoparticulate metal oxide acceptor (QD-MO) system. The functional form of this many-state Marcus model is as follows:…”
Section: Modeling Electron Transfer In Qd-mo Nanoparticulate Systemsmentioning
confidence: 99%
“…13,29,30 Instead, the atomic-scale electronic coupling and transient interfacial electronic structure are believed to play key roles in determining the device function. [9][10][11][12][13]31 Ultrafast time-domain studies in the optical, infrared, and terahertz regimes have identified distinct differences between the dynamic response of dye−ZnO and dye−TiO 2 interfaces. 5,[8][9][10][11][12][13]17 In particular, transient signals from ZnO-based dye-sensitized systems are marked by prominent "slow" components, which evolve on time scales ranging from a few to hundreds of picoseconds.…”
Section: 23−26mentioning
confidence: 99%
“…In such devices, the photoinduced electron-transfer (ET) reactions at the dye-semiconductor interface, in particular the processes of electron injection from an electronically excited state of a chemisorbed dye molecule into the semiconductor substrate, represent a key step for photonic energy conversion [33][34][35][36][37][38] . In recent years, photoinduced ET processes in dye-semiconductor systems have been studied in great detail experimentally with femtosecond spectroscopy techniques 34,35,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] . It has been shown that electron-injection processes at the dye-semiconductor interfaces often take place on an ultrafast sub-picosecond timescale 37,43,45,46,57,58 .…”
Section: Introductionmentioning
confidence: 99%